Pengaruh Job Demands Dan Perceived Organizational Support Terhadap Work Engagement Pada Tenaga Kesehatan Di Rumah Sakit Umum Daerah Provinsi Sulawesi Barat - Erwin, Muh.; Ferils, Muh.; Burung, Rachmat; Dahri, Nur Wahyunianti; Junaeda, Junaeda (Jurnal Economic Resource, 2025)
This study aims to analyze the effect of job demands and perceived organizational support on work engagement among healthcare workers at the Regional General Hospital of West Sulawesi Province. The study employed a quantitative method with an associative approach. The population consisted of 374 healthcare workers, with a sample of 79 respondents determined using Slovin’s formula and incidental sampling. Data were collected through observation, interviews, documentation, and questionnaires. Validity and reliability tests were conducted to ensure the quality of the instruments. Data analysis was performed using multiple linear regression, with hypothesis testing conducted through partial test (t-test), simultaneous test (F-test), and the coefficient of determination (R²). The results indicate that job demands have a positive and significant partial effect on work engagement. Similarly, perceived organizational support also shows a positive and significant partial effect. Simultaneously, job demands and perceived organizational support significantly influence work engagement, contributing 42%, while the remaining 58% is explained by other factors outside the research model, which represents a limitation of this study. These findings highlight that the balance of work demands and perceived organizational support plays a crucial role in enhancing employee engagement.